Sociocultural Foundations of Disruptive Dehavior - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The modern world is experiencing rapid and contradictory processes of transformation that affect all areas of human life. These processes provide more food for thought than any other period has ever provided. As much as the era is oversaturated with scientific discoveries, we cannot help but notice that the absolutism from the spiritual (moral) to the bankrupt rationality is hopeless and destructive for humanity. The mind without complete moral control satisfies the needs of the human individual for physical existence (mainly biological) and can lead to the psychological regression of the individual. The increase in destructiveness in post-industrial societies is perhaps the price that man pays for rejecting traditional norms, ignoring moral and ethical guidelines. The wars going on in the world, the terrorist acts and revolutions, the increase in crime and the ecological disasters are the evidence that destructiveness and aggression have become the characteristics of the current civilization. It is indisputable that the source, driving force and result of this crisis is man. In this case, it is necessary to understand how a situation is possible when a person, as an active creative being, becomes a destroyer who nullifies the possibility of his own existence. If a person who has adopted a destructive culture does not stop and cannot find a "key" that will enable him to remain in the present, as well as to open the door to the near future, he can destroy not only himself, but also the entire humanity.
Keywords: culture of life; destructive person; destructive behavior; destructive communication; man-beast; social insanity